2012
DOI: 10.1111/cns.12053
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Induces Neuroprotection in 6‐OHDA‐Lesioned PC12 via the PI3K/AKT/Caspase 3 Pathway and Anti‐Inflammatory Responses

Abstract: Our results demonstrate that simvastatin provides robust neuroprotection against dopaminergic neurodegeneration, partially via antiinflammatory mechanisms and the PI3K/Akt/caspase 3 pathway. These findings contribute to a better understanding of the critical roles of simvastatin in treating PD and might elucidate the molecular mechanisms of simvastatin effects in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 53 publications
(63 reference statements)
4
49
0
Order By: Relevance
“…Cotreatment with LY294002, the inhibitor of PI3K, blocked the up-regulation of p-Akt and p-GSK-3β protein expressions as well as deregulation of NSC apoptosis by simvastatin, indicating that PI3K/Akt/GSK-3β signaling pathway is involved in the neuroprotection of simvastatin against isoflurane-induced NSC apoptosis. This is similar to the findings that simvastatin played in other models [56,57]. Whether the protective effects of simvastatin is merely due to the increase in Akt phosphorylation or the decrease in Akt and GSK-3β dephosphorylation needs to be studied further.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 85%
“…Cotreatment with LY294002, the inhibitor of PI3K, blocked the up-regulation of p-Akt and p-GSK-3β protein expressions as well as deregulation of NSC apoptosis by simvastatin, indicating that PI3K/Akt/GSK-3β signaling pathway is involved in the neuroprotection of simvastatin against isoflurane-induced NSC apoptosis. This is similar to the findings that simvastatin played in other models [56,57]. Whether the protective effects of simvastatin is merely due to the increase in Akt phosphorylation or the decrease in Akt and GSK-3β dephosphorylation needs to be studied further.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 85%
“…Our previous study on simvastatin (Sim) therapy involving patients with PD confirmed that Sim is able to modulate NMDA receptors [8] and protect against dopaminergic neurodegeneration through the PI3K/Akt/caspase 3 pathway [9]. In a related study, we observed that the anti-oxidative stress function of Sim in dopaminergic neurons is very prominent.…”
Section: Introductionmentioning
confidence: 82%
“…In addition to lowering cholesterol, statins have gradually been used to reduce the risk of heart attack, cerebral ischemia, and have been demonstrated to exert potential beneficial effects in different neurological diseases (Wang et al, 2007;Keener & Sanossian, 2008;van der Most et al, 2009;Sugawara et al, 2011;Ayer et al, 2013). Although the precise mechanisms are unclear and contrasting results have been observed (Reiss & Wirkowski, 2007;Becker et al, 2008), additional studies have found that statins display important effects on cognitive related neurological diseases such as PD van der Most et al, 2009;Wang et al, 2011;Lee et al, 2013;Xu et al, 2013). If statins would have a potentially useful impact on impaired memory regulation in the progression of PD, this presents an interesting challenge.…”
Section: Introductionmentioning
confidence: 99%